Performance-Based Seismic Fragility and Residual Seismic Resistance Study of a Long-Span Suspension Bridge - Fangwen Wu; Jianfei Luo; Wei Zheng; Cheng Cai; Jun Dai; Yajun Wen; Quanyou Ji (Advances in Civil Engineering)
Earthquakes can cause serious damage to traffic infrastructure and even induce the collapse of bridges, which is even worse. At the same time, earthquakes are key factors to the overall service capacity of the traffic network. Therefore, mastering the failure mechanism and evaluating accurate residual seismic resistance of a bridge under earthquakes are of great significance to the rapid recovery of traffic network function. For this reason, a performance-based methodology for the evaluation of the residual seismic resistance of a suspension bridge is proposed. In this paper, we provide the fragility curves of the key sections of the pier by incremental dynamic analysis (IDA), mathematical statistical analysis, and the damage law and obtained the failure state of the structure and the overall seismic capacity residual ratio and the stage seismic capacity residual ratio of the structure. Then, based on the research results of IDA, the reserve seismic capacity is analyzed as well. The research results explore a new method to accurately estimate the residual seismic capacity for resilience assessment.